Lifecycle, Iteration, and Process Automation with SMS Gateway - Fenny Fenny (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Producing a better quality software system requires an understanding of the indicators of the software quality through defect detection, and automated testing. This paper aims to elevate the design and automated testing process in an engine water pump of a drinking water plant. This paper proposes how software developers can improve the maintainability and reliability of automated testing system and report the abnormal state when an error occurs on the machine. The method in this paper uses literature to explain best practices and case studies of a drinking water plant. Furthermore, this paper is expected to be able to provide insights into the efforts to better handle errors and perform automated testing and monitoring on a machine.